2011
DOI: 10.1371/journal.pone.0021533
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Induced JNK Activation Is a Critical Event Leading to Mitochondria-Mediated Cell Death Caused by β-Lapachone Treatment

Abstract: Backgroundβ-lapachone (β-lap) is a bioreductive agent that is activated by the two-electron reductase NAD(P)H quinone oxidoreductase 1 (NQO1). Although β-lap has been reported to induce apoptosis in various cancer types in an NQO1-dependent manner, the signaling pathways by which β-lap causes apoptosis are poorly understood.Methodology/Principal Findingsβ-lap-induced apoptosis and related molecular signaling pathways in NQO1-negative and NQO1-overexpressing MDA-MB-231 cells were investigated. Pharmacological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
2
37
1
Order By: Relevance
“…75 The results from our experiments and the previous literature suggest that AgNPs can reduce the membrane potential of MDA-MB-231 cells. 73 …”
mentioning
confidence: 99%
“…75 The results from our experiments and the previous literature suggest that AgNPs can reduce the membrane potential of MDA-MB-231 cells. 73 …”
mentioning
confidence: 99%
“…After serum starvation for 18 h, the cells were pretreated with HMC05 in the presence or absence of inhibitor for 1 h. The various concentrations of XO (10,20,30,40 and 50 munit/mL) with 0.5 mM xanthine were added to each well at 1 h after HMC05 treatment, after which the cells were incubated for an additional 18 h. Next, MTT (5 mg/mL) was incubated for an additional 2 h. The cell culture medium was then aspirated and the cells were solubilized in 200 µL dimethyl sulfoxide. Finally, an absorbance of 550 nm was measured using an ELISA reader (Bio-Tek Instruments, Winooski, VT, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…16,19,20) To identify the signaling pathway involved in HMC05-mediated NQO-1 induction, we assessed the effects of selective chemical inhibitors of signaling via MAPKs, PI3K, GGTase 1 and farnesyltransferase (FTase). Interestingly, the inhibitors of extracellular signal-regulated kinase (ERK) (PD98059), p38 MAPK (SB203580), JNK (JNK inhibitor II) and PI3K (LY294001 and wortmannin) had no effects on HMC05-mediated NQO-1 induction (Fig.…”
Section: The Reversal Of the Protective Effect Of Hmc05 Through The Imentioning
confidence: 99%
“…Interestingly, surface chemistry role during clearance or uptake in circulation accommodates the facilitation of nanotherapeutic carriers when an abundance of small nanoparticles exist within the malignancies [37]. Studies revealed that nanoscale Ag particles had shown a prolonged circulation type of the half-life nanoparticles which can escape from affected cell in the tissue effectively.…”
Section: Nanoscale Silver Particlesmentioning
confidence: 99%